Nutritional status and early childhood caries in children 0-3 years: Review of the literature - Arévalo Illescas, Paola Lisseth (2021)
Objective: To compile information relating nutritional status and early childhood caries in children aged 0 to 3 years. Materials and methods: Search was made of scientific articles from November 2020 to January 2021 in both Spanish and English in databases such as: Google Scholar, Scielo, Pubmed, Dialnet, Science Direct, with the use of the keywords: dental caries, eating behavior, breastfeeding, demineralization, sucrose. Including original articles and literature review articles. Excluding articles that did not pertain to the subject of nutrition and caries. Results: Early childhood caries begins shortly after tooth eruption and is most frequently transmitted vertically (from mother to child), with Streptococcus mutans, being the most cariogenic microorganism. It has been demonstrated in several studies that malnutrition is not related to early childhood caries, but excessive consumption of sugars, breastfeeding and frequent nighttime bottle-feeding are. For this reason, fluoride toothpastes (1000-1100 ppm of fluoride) should be used in infants between 0 and 3 years of age in order to eliminate bacterial plaque and the formation of dental caries. Conclusions: There is a close relationship between nutrition and dental caries in children 0-3 years of age, but the most important factor is the intervention of parents in the application of oral care in infants; it is important to know the sugar content of foods in order to prevent the development of early childhood caries.